2005
DOI: 10.1002/nau.20188
|View full text |Cite
|
Sign up to set email alerts
|

Bladder dysfunction in patients with cauda equina lesions

Abstract: Our study demonstrated significant LUT dysfunction, which disturbed the life of the majority of patients with chronic lesions of the cauda equina. Due to poor correlation between patients' symptoms and urodynamic findings cystometric surveillance is proposed in all patients with significant cauda equina lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 33 publications
3
42
0
3
Order By: Relevance
“…For perianal sensation, a composite score was produced by summation of scores from both sides. 5,6 The penilo-cavernosus reflex was elicited by brisk compression of the glans penis between the first three fingers. Movement of the perineum was carefully observed, and if an unequivocal response could be seen, the reflex was regarded as normal.…”
Section: Methodsmentioning
confidence: 99%
“…For perianal sensation, a composite score was produced by summation of scores from both sides. 5,6 The penilo-cavernosus reflex was elicited by brisk compression of the glans penis between the first three fingers. Movement of the perineum was carefully observed, and if an unequivocal response could be seen, the reflex was regarded as normal.…”
Section: Methodsmentioning
confidence: 99%
“…Linear regression showed that the loss of perineal sense and female sex have a positive impact on patients' urinary incontinence. The study concluded that due to poor communication between urodynamic study fi ndings and the symptoms, it does not have induction in the diagnosis of disease (20). In a study by Lazaaro et al in 2004, eff ects and changes of electromy- Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…To score the severity of sacral dysfunctions, Slovene versions of the standard urinary incontinence [3,5], anal incontinence [6], constipation [1], and male sexual dysfunction [16] questionnaires were used [9,14,15]. In all patients clinical examination was performed with emphasis on the lower limbs and sacral segments [13].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, bladder, bowel, and sexual functions may also be disturbed [9,14,15,17]. The annual incidence rate of cauda equina lesions has been estimated at 3.4 per million population, and the period prevalence at 8.9 per 100,000 [11].…”
Section: Introductionmentioning
confidence: 99%